Epidemiology, clinical features and risk factors for human rabies and animal bites during an outbreak of rabies in Maputo and Matola cities, Mozambique, 2014: Implications for public health interventions for rabies control - Salomão, Cristolde; Nacima, Amílcar; Cuamba, Lutero; Gujral, Lorna; Amiel, Olga; Baltazar, Cynthia; Cliff, Julie; Gudo, Eduardo Samo (PLOS Neglected Tropical Diseases, 2017)
Background In Mozambique, the majority of rabies outbreaks are unreported and data on the epidemiological features of human rabies and animal bites are scarce. An outbreak of human rabies in adjacent Maputo and Matola cities in 2014 prompted us to investigate the epidemiology, clinical features and risk factors of human rabies and animal bites in the two cities. Methodology/Principal findings We reviewed cases of human rabies and animal bites from April to July 2014, and carried out a community investigation in July and August in the neighborhoods where cases of human rabies resided. This investigation included collection of clinical, demographic and epidemiological information and a case control study to investigate the risk factors associated with human rabies. Fourteen cases of human rabies were detected in Maputo (n = 10) and Matola (n = 3) cities and neighbouring Boane district (n = 1) between April and August 2014, all of whom had been admitted to hospital. All had a recent history of dog bite. Of the 14 rabid dogs, only one had been immunized. 819 cases of animal bites were registered, of which 64.6% (529/819) were from Maputo City. Dogs were responsible for 97.8% (801/819) of all animal bites, but only 27.0% (126/467) were immunized. Factors significantly associated with human rabies were: age <15 years (p = 0.05), bite by stray dog (p = 0.002), deep wound (p = 0.02), bite in the head (p = 0.001), bite by unimmunized dog (p = 0.01), no use of soap and water (p = 0.001), and no post-exposure prophylaxis (p = 0.01). Conclusions/Significance Implementation of control measures for rabies is poor in Maputo and Matola cities, where cases of human rabies were strongly associated with bites by stray and unvaccinated dogs and irregular implementation of post-exposure measures.